FAKTOR-FAKTOR YANG MEMPENGARUHI BIAS GENDER PENGGUNAAN KONTRASEPSI PADA PASANGAN USIA SUBUR DI DESA DAWAN KALER KECAMATAN DAWAN KLUNGKUNG - Dalem, Dewa Nyoman (PIRAMIDA; Vol 8, No. 2 Desember 2012, 2013)
Inequality of contraceptive uses and the wives has become a problem, not only at the local, but also in and even global levels. This imbalance has occurred since the inception of family planning (Keluarga Berencana) program in the 1970’s in which the target users of contraception has been always the women (wives). The low participation of husbands in contraceptive use in the family occurred to date. If this issue does not get immediate attention, then it is tantamount to depriving,women of their reproductive health rights, and allowing gender inequality to grow in the husband-wife relationship. This motivates the study concerning gender bias in the use of contraceptives among couples of childbearing-age, taking the location of Dawan Kaler village, Dawan district of Klungkung regency. This study examines one principle issue, namely: The factors influencing gender bias in contraceptive use among couples of childbearing-age in Dawan Kaler village, Dawan District of Klungkung regency. To uncover the problem above, this study uses qualitative methods employing data collection techniques by means of observation, in-depth interviews, documented study as well as focused group discussion (FGD). In analyzing the problems, the theories of hegemony and socialist feminism are used. The result of the study shows that the factors influencing the gender bias in the use of contraceptives among couples of childbearing-age in Dawan Kaler village include the patriarchal culture, traditions, the wives concerns over the use of contraceptives by the husbands, gender ideology, and the husband egotistical attitude that is difficult to change
Keywords: gender bias; contraception; and couples (husband and wife)